Transport and logistics in Dubai: A high stakes play - Thorpe, Michael; Mitra, S. (IGI Global, 2011)
Over the past decade, the Emirate of Dubai has emerged as a leading transport and logistics centre serving not only the Middle East and North Africa (MENA) region, but also Russia, Europe, Asia, and the Far East. This has been the result of a concerted and far-sighted government initiative that, since the mid-1970s, has sought to diversify an economy underpinned by oil revenues, but with little else in terms of domestic resource endowments (Economist.com, n.d.). The population is very small in number and relatively un-skilled, there is little arable land, and historically, there was no industrial base. Until the discovery of oil in the 1960s, Dubai was essentially a pearling port and regional entrepot based around shipping. A succession of formal government plans has introduced incentives and inducements aimed at encouraging companies to set-up operations in the emirate with the aim of fast-tracking the establishment of a modern, service-based economy. Initially the planning focus was on establishing the finance, tourism, and property sectors as well as on significant expansion and upgrading of traditional trading activities. More recently the emphasis has broadened to incorporate more technology-intensive service industries.Transport and Logistics in Dubai: The phased development of Dubai’s transport and logistics sector over the past several decades has culminated in the establishment of a major regional commercial hub, a so-called “aerotropolis”. Although a work-in-progress, several stages of this long-term project are already operational, and construction remains ongoing. The future success of this government project is unclear. In the public sector, there exist major challenges, some reflective of the need to efficiently manage and coordinate such a huge undertaking while others stem from the uncertainties of a competitive global market-place. For individual companies and industries (public and private) looking to participate and commit to the venture, a number of issues need to be addressed in the formulation of business strategies.